Revisiting the theory of patet in Sundanese karawitan: between academic theory and artistic practice - Marsel Ridky Maulana; Regina Darmawanti (Gelar: Jurnal Seni Budaya, 2025)
The ongoing debate surrounding patet theory in Sundanese karawitan reveals a clear divergence in epistemic perspectives between formal music education and artistic practice. Within academic settings, patet is positioned as a theoretical foundation for performing the pelog-salendro gamelan system. However, many practitioners argue that the concept does not manifest explicitly in lived musical practice. This study re-examines the theoretical construction of patetthrough an ethnomusicological lens, drawing on practice theory (Bourdieu; Reckwitz) and the concept of embodied musical knowledge (Brinner; McKerrell). Findings demonstrate significant differences regarding nada pangaget and pancer: academics tend to codify both as fixed elements, whereas artists interpret them relationally, guided by musical intuition and performative context. The analysis confirms that patet continues to shape tonal orientation, dominant tones, and affective musical space. This study argues that patet should be understood as a dual concept, normative in academic discourse yet flexible in artistic practice, bridging theoretical frameworks and Sundanese karawitan performance.